2002
DOI: 10.1021/ja017319j
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Catalyzed Polymerization

Abstract: Native DNA oligomers are shown to be stereoselective catalysts for the polymerization of 5'-amino-3'-acetaldehyde-modified thymidine/adenosine nucleosides through reductive amination. The reaction follows step-growth kinetics to read the encoded sequence and chain-length information in the antiparallel direction. Single mismatches in the template are selected against at a level of >100:1. A method is therefore established to translate biopolymer-encoded information stereoselectively into sequence- and chain-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
127
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 6 publications
3
127
0
6
Order By: Relevance
“…In this scenario, oligonucleotide ligation together with gap filling reactions involving monomers and shorter oligomers, would lead to product strand synthesis. The final stages of product strand assembly could therefore involve only a few bond-forming steps, and could occur quite rapidly (for an excellent example in a non-RNA model system, see [43,44]). The fidelity of complementary strand synthesis in this manner is unclear.…”
Section: Rate Of Template Copying Chemistrymentioning
confidence: 99%
“…In this scenario, oligonucleotide ligation together with gap filling reactions involving monomers and shorter oligomers, would lead to product strand synthesis. The final stages of product strand assembly could therefore involve only a few bond-forming steps, and could occur quite rapidly (for an excellent example in a non-RNA model system, see [43,44]). The fidelity of complementary strand synthesis in this manner is unclear.…”
Section: Rate Of Template Copying Chemistrymentioning
confidence: 99%
“…For example, a single strand of DNA can selectively bind and orient two smaller complementary strands to direct their respective reactive appendages (9)(10)(11)(12). Additionally, single-and double-stranded DNA as well as RNA are capable of catalyzing polymerization or ligation of complementary sequences through duplex and triplex recognition and assembly (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…However, all these difficulties can be circumvented by the use of a linker chemistry that initially forms a low-energy, reversible bond, allowing for selection of the thermodynamic product (i.e., in the case of RNA, the WatsonCrick base-paired product). One remarkable example of the power of reversible linkages was provided by Lynn and coworkers, who showed that 5 0 -deoxy,5 0 -amino, 3 0 -deoxy, 3 0 -formylmethyl-dT could polymerize via reductive amination in aqueous solution (Li et al 2002). Polymerization occurred only in the presence of a d(A 8 ) template; without a template, no oligomer product was detected.…”
Section: Primitive Genetic Polymersmentioning
confidence: 99%
“…Mechanisms for recycling are easy to imagine, if the covalent bonds that joined the molecular components of proto-biopolymers could have been formed, broken and re-formed repeatedly. Such a process would have allowed proto-biopolymers to be created that were thermodynamically favored structures (Li et al 2002;Hud et al 2007;Ura et al 2009) and for "errors" in synthesis to be corrected (e.g., replacement of non-or mispaired nucleobases with pairing ones). Proto-RNA monomers might have even been repeatedly recycled into polymers with different nucleotide sequences (and corresponding functions) as survival pressures changed (Ura et al 2009 We now will discuss the three molecular components of nucleic acid polymers and consider the implications of the three hypotheses presented earlier in considering alternative candidates for proto-RNA.…”
mentioning
confidence: 99%